2015
DOI: 10.1111/jcc4.12109
|View full text |Cite
|
Sign up to set email alerts
|

The Extended iSelf: The Impact of iPhone Separation on Cognition, Emotion, and Physiology

Abstract: This study uniquely examined the effects on self, cognition, anxiety, and physiology when iPhone users are unable to answer their iPhone while performing cognitive tasks. A 2 x 2 within-subjects experiment was conducted. Participants (N = 40 iPhone users) completed 2 word search puzzles. Among the key findings from this study were that when iPhone users were unable to answer their ringing iPhone during a word search puzzle, heart rate and blood pressure increased, self-reported feelings of anxiety and unpleasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
185
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(233 citation statements)
references
References 26 publications
(37 reference statements)
9
185
2
8
Order By: Relevance
“…In addition, the application of fMRI techniques to examining adolescent social media use will add a level of complexity and greater nuance to our understanding of these processes, as has been shown in preliminary work (e.g., Sherman et al 2016). Measures of physiological activity, including heart rate and blood pressure, have also recently been applied to examining adults’ experiences of stress when separated from their cell phones (Clayton et al 2015); similar measures may provide insight into adolescents’ physiological response to social media. That said, continued descriptive work will be invaluable in this area.…”
Section: Building On the Transformation Framework: Methodsological Conmentioning
confidence: 99%
“…In addition, the application of fMRI techniques to examining adolescent social media use will add a level of complexity and greater nuance to our understanding of these processes, as has been shown in preliminary work (e.g., Sherman et al 2016). Measures of physiological activity, including heart rate and blood pressure, have also recently been applied to examining adults’ experiences of stress when separated from their cell phones (Clayton et al 2015); similar measures may provide insight into adolescents’ physiological response to social media. That said, continued descriptive work will be invaluable in this area.…”
Section: Building On the Transformation Framework: Methodsological Conmentioning
confidence: 99%
“…Przybylski, Murayama, DeHaan, and Gladwell (2013), who created the FoMO scale, concluded that individuals high in FoMO use social media sites more and are more likely to use their phones whilst driving a vehicle or sitting in a classroom. FoMO has been found to increase social media use in young people (Alt, 2015;Przybylski et al, 2013;Vaidya, Jaiganesh, & Krishnan, 2016), and some studies show that FoMO also was the variable most related to problematic smartphone usage (Alt, 2015;Clayton, Leshner, & Almond, 2015;Elhai et al, 2016;Przybylski et al, 2013). Gokler, Aydın, Ünal, and Metintaş (2016) also found a positive relationship between the increase in the frequency of social network use and FoMO.…”
Section: Smartphone Addiction Fomo and Sns Usementioning
confidence: 97%
“…72 In regard to texting and phone use, recent evidence suggests that separation from the ability to communicate with others by modern technology can itself cause distress. 73 In short, the ability to participate in normal activity appears to be a critical and independent determinant of psychological well-being for individuals after injury or illness. Yet contemporary clinical management of concussion does not adequately consider the potential negative impact of prolonged activity restriction on physical and emotional health.…”
Section: Possible Harmful Effects Of Restmentioning
confidence: 99%